Socioeconomic and Ethnic Disparities in Periocular Cutaneous Malignancies. (3rd July 2016) - Broadbent, Talmage; Bingham, Brian; Mawn, Louise A.
ABSTRACT: Cutaneous malignancies make up the majority of periocular tumors diagnosed and treated by ophthalmologists. In this review, we examine literature regarding ethnic and socioeconomic disparities in incidence and clinical outcomes of the three most common cutaneous periocular tumors: basal cell carcinoma, squamous cell carcinoma, and melanoma. In all three tumor types, the literature shows an increased incidence among two groups: those with lightly pigmented skin and those of higher socioeconomic status. While incidence is high in these groups, clinical outcomes for these patients tend to be good. Those with lower socioeconomic status and ethnic minorities, on the other hand, have a low incidence but are more likely to have poor clinical outcomes. These disparities are likely the result of both biologic and behavioral differences between patients and could provide opportunities for intervention to change risk perception and improve outcomes.